An unusual radiological manifestation of a mandibular central giant cell granuloma - Admani, Bushra Ali; Siddiqui, Fatima; Ahmed, Huda; Hameed, Marya (International Journal of Scientific Reports, 2023)
Central giant cell granuloma (CGCG) is an uncommon benign osseous lesion of the jaw. We present the case of an aggressive CGCG in a 16-year-old boy with a 5-month history of facial swelling and nasal obstruction. He was referred for a radiology consult for multiple expanding swellings on the right hemi-face. The swellings were reported to have an insidious onset, slow progression and no association with paresthesia, nasal discharge, or systemic symptoms. Extra oral examination revealed a diffuse swelling on the right side of the face which obliterated the nasolabial fold causing facial asymmetry. A face and neck computed tomography (CT) showed expansile multi loculated lytic lesions of the right mandibular ramus which involved the condyle and hard palate. Similar lesions were also found in the skull base. Scans showed fine internal septations and internal ground glass haze. It also revealed involvement of several teeth roots and surrounding soft tissues. A pre-operative intra-oral biopsy of the lesion revealed multinucleated giant cells, comprising of both spindle-shaped and round cells. Differential diagnosis helped determine the lesions as CGCG. This case helps to demonstrate the wide variation in the clinical, radiological, and histopathological features of CGCG and the importance of thorough investigation for timely diagnosis.